Chronic Neck Pain and Cervico-Craniofacial Pain Patients Express Similar Levels of Neck Pain-Related Disability, Pain Catastrophizing, and Cervical Range of Motion. (29th March 2016) - Muñoz-García, Daniel; Gil-Martínez, Alfonso; López-López, Almudena; Lopez-de-Uralde-Villanueva, Ibai; La Touche, Roy; Fernández-Carnero, Josué
Abstract : Background. Neck pain (NP) is strongly associated with cervico-craniofacial pain (CCFP). The primary aim of the present study was to compare the neck pain-related disability, pain catastrophizing, and cervical and mandibular ROM between patients with chronic mechanical NP and patients with CCFP, as well as asymptomatic subjects. Methods. A total of 64 participants formed three groups. All participants underwent a clinical examination evaluating the cervical range of motion and maximum mouth opening, neck disability index (NDI), and psychological factor of Pain Catastrophizing Scale (PCS). Results. There were no statistically significant differences between patients with NP and CCFP for NDI and PCS (P > 0.05 ). One- way ANOVA revealed significant differences for all ROM measurements. The post hoc analysis showed no statistically significant differences in cervical extension and rotation between the two patient groups (P > 0.05 ). The Pearson correlation analysis shows a moderate positive association between NDI and the PCS for the group of patients with NP and CCFP. Conclusion. The CCFP and NP patient groups have similar neck disability levels and limitation in cervical ROM in extension and rotation. Both groups had positively correlated the NDI with the PCS.